Ocean Bottom Sampler for Ships under Way - Worzel, J. L. (The International Hydrographic Review, 2018)
A simple bottom sampler has been developed which may be used from ships under way at speeds up to 12 knots. The sampler is allowed to fall freely under its own weight, and is recovered by reeling in a wire attached to the front. An open tube at the front will obtain about % pint of surface material from mud, sand, gravel, or coral bottoms. Existing models have been used in depths to 300 fathoms. At a speed o f 8 knots, using a winch a 3/4 h-p. motor, one man can take a sample in 3 minutes in 10 fathoms of water, and in 8 minutes in 100 fathoms. Models have been built with trap doors to close thé tube after taking the sample» and to allow the water in the tube to escape when the sample is taken. These have been discarded as the improvement in the samples was negligible. The sampler can be easily combined with free-falling hydrographic instruments, such as the bathythermograph. Operation under way improves the ease and accuracy with which the position of a sample may be fixed as the ship can maintain its speed and course. It greatly increases the area covered and the number of samples taken in a given time.